Pendampingan Pastoral dengan Teori Gestalt Kepada Wanita yang Mengalami Stres Karena KDRT (Jurnal Pendidikan Agama dan Teologi, 2024)
Pastoral assistance using a Gestalt theory approach to women who experience stress due to "Domestic Violence" is an important effort in assisting victims of violence holistically. Gestalt theory, which emphasizes full awareness of one's own experiences and the surrounding environment, can provide an in-depth approach to help individuals understand the feelings, behavior and relationship patterns that are formed as a result of the violence they experience. This assistance aims to provide spiritual, emotional and psychological support through an approach that focuses on the victim's current experience and self-recovery.This mentoring process begins with building safe and understanding relationships, as well as providing space for women to talk about their experiences without fear of being judged. In assistance sessions, Gestalt techniques such as the “empty chair” can be used to help victims face and express their feelings of oppression, as well as increase awareness of their inner strength to overcome stress and trauma. Apart from that, the spiritual aspect is also an inseparable part in providing comfort and hope, as well as helping victims find greater meaning and purpose in life despite difficulties. It is hoped that the results of this assistance will help women victims of domestic violence to gain emotional recovery, increased self-esteem, and the ability to make healthier decisions in their relationships. Pastoral care using the Gestalt approach provides a comprehensive approach by combining psychological, emotional and spiritual aspects, so that it can support women to overcome the stress that arises from experiences of domestic violence.